Is urban bushmeat trade in Colombia really insignificant?. Issue 2 (4th March 2016) - van Vliet, Nathalie; Quiceno, Maria; Moreno, Jessica; Cruz, Daniel; Fa, John E.; Nasi, Robert
Abstract: The bushmeat trade in ecosystems in South America other than those within the Amazon basin is presumed to be insignificant, as alternative sources of protein (e.g. beef, chicken, fish) are considered to be more readily available in non-moist forests. However, studies and confiscation reports from countries such as Colombia suggest that bushmeat is consumed in a variety of ecosystems, although the nature of market chains, particularly in urban areas, is still unknown. We studied the urban bushmeat trade in markets in the five main ecoregions in Colombia. We recorded a total of 85 species, the most frequently traded being the paca Cuniculus paca, red brocket deer Mazama americana, grey brocket deer Mazama gouazoubira, capybara Hydrochoerus hydrochaeris, armadillo Dasypus spp. and black agouti Dasyprocta fuliginosa . Most sales of wild meat occur through clandestine channels and involve a limited number of stakeholders. Bushmeat is a luxury product in urban areas of the Caribbean, the Pacific and the Andean regions. Further work is needed to quantify and monitor the volumes of bushmeat traded, comprehend motivations, explore ways of reducing threats, and engage with stakeholders to organize legal and sustainable use of bushmeat.